Cortisol level decreases natural killer cell activity among women with aircraft noise - Hartono, Hartono (Faculty of Medicine, Trisakti University, 2010)
One of the impacts of exposure to noise is stress. Natural killer (NK) cells are one of the leukocyte subsets that are responsive to physiological and psychological stress. The objective of the present research was to determine the relationship between cortisol levels and NK cell activity among women with aircraft noise stress in the area of Adi Sumarmo Airport, Solo. This study was an analytical survey with a cross sectional design. The number of subjects was 39, who were divided into 3 groups of 13 subjects each. Groups 1 to 3 were exposed to noise levels of 92.29 dB, 71.79 dB and 52.17 dB, respectively. The sample was taken using simple random sampling. The data were analyzed by Pearson correlation test and Anova followed by post hoc test using LSD test. The Anova test showed that there were significant differences in circulating cortisol levels among all groups (p = 0.018). The Pearson correlation test showed that there was a positive association between circulating cortisol levels and the number of NK cells (r = 0.547; p< 0.05) and a negative association between circulating cortisol levels and NK cell activity (r = - 0.578; p < 0.05). This study indicated that cortisol levels decreased NK cell activity among women with exposure to aircraft noise. Women who experienced aircraft noise stress showed increased cortisol levels and decreased NK cells activity.